Why, when and how to implement value-based pricing in a retail company : Case Nordic retail company - Laukkanen, Eero (My University, 2021)
Pricing is a critical process for any company and it has a significant affect to profitability. When compared to its relevance, it can be seen to be underappreciated by both the academ-ics and the practitioners. The different pricing methods in use can be divided under three orientations: cost-based, competition-based and value-based. Value-based pricing is the newest of the orientations. Recent pricing literature states that when compared to the other orientations, using it should lead to superior results. However, value-based pricing is the significantly least used pricing orientation in practice. Retail industry is a good example of a field where academic world suggests that the use of value-based pricing would be beneficial, but it has not found its way to the practices of the companies’. This study aims to explore why and when should a retail company consider the use of value-based pricing and how should they approach its implementation. This research is conducted as a qualitative case study with one case subject and an ac-tion-oriented methodological approach. The case company is a large retailer operating in the Nordic markets. Its pricing practices are typical for a company operating in this field, but the organization is also interested in exploring new ways of pricing. The empirical data for this study is collected via in-depth semi-structured interviews. This thesis suggests that the primary reason for a retail company to consider the use of value-based pricing is to aim for better profitability. This pricing orientation also supports well wider customer-oriented ambitions. The value-based pricing is best used when some differentiative factor can be found between the commodity being priced and the other substi-tutes on the markets. The differentiative factor does not necessarily need to be directly linked to the offering, it can also be tied to for example the customer experience or the image of the company. On the question of how the implementation of the value-based pricing should be approached, this thesis found that many of the suggestions are applicable to any kind of a bigger change initiative. The endeavour should not be underestimated, and sufficient re-sources should be reserved for it. Good change management capabilities are the single most significant factor in ensuring of a successful implementation of value-based pricing.
Keywords: Pricing, value-based pricing, strategic pricing, pricing decisions